PENERAPAN METODE PEMBELAJARAN EKSPERIMEN UNTUK MEREMEDIASI MISKONSEPSI SISWA TENTANG GETARAN DI SMA - Cimparing, Cicy (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
Â AbstractThis study aims to determine the effectiveness of the experimental teaching methods to remediate misconceptions students on vibration material in class X SMA 6 Pontianak. The method used an experimental method with pre Experimental Design draft form one group pretest-posttest with sample class X MIA 3 totaling 29 students selected at intact group. The average percentage decrease in the number of students who have misconceptions of 78.37%. The conception is found (100%) in the second indicator, the students assume that the mass effect on the frequency and amplitude of the pendulum. Based on an analysis using prices obtained McNemar test Â the conception significant changes between before and after remediation implemented using experimental teaching methods. The effectiveness of the experimental teaching method is calculated using Decreasing of Quantity student that Misconseption (DQM) with a value of 78.3 (high). This research is expected to be used as an alternative form of re-learning remediation activities in order to overcome the misconception experienced by students.Â Keywords: Remediation, misconceptions, experimental learning method, vibration